Prediksi Financial Distress menggunakan Metode Altman Z-Score Modifikasi pada Anak Perusahaan PT XYZ yang Melakukan Impor Tahun 2020-2024 - Nastiti Putri Pertiwi; Anita Handayani (Universitas Nusantara PGRI Kediri, 2025)
This study predicts the financial condition of PT XYZ's subsidiaries, particularly those engaged in import activities, in the 2020-2025 period. The phenomenon of exchange rate fluctuations has more or less affected the company's performance in both the short and long term. This study aims to identify the company's financial health before the potential for bankruptcy arises. Using a quantitative approach with descriptive methods, this study collected data through interviews and documentation. The object of the study was the annual financial report of PT YKP for the 2020-2025 period. The data analysis tool used Microsoft Excel with the Modified Altman Z-Score formula model that uses 4 (four) financial ratios, namely the Working Capital to Total Assets Ratio, the Retained Earnings to Total Assets Ratio, the Earnings Before Interest and Tax to Total Assets Ratio, and the Equity to Total Liabilities Ratio. The calculation results will show the category of the company being in a safe condition, a gray zone, and in a difficult condition. The results of the study indicate that in the past year, namely in 2024, the company's financial condition has decreased and the Z-Score of PT XYZ's subsidiaries that carry out imports is in the gray zone.